HEKSACOPTER PENCITRAAN UDARA BERTEKNOLOGI GPS - Wardana, Christian Setya; Wicaksono, Basilius Kristiawan; Muharya, Ganda Adityo (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Nowadays the need of aerial photography increased. Heksacopter is a vehicle of development from helicopter which has 6 blades as their actuators. Heksacopter can do aerial photography well because it has a good level of stability. An advanced technology is added to Heksacopter to support the aerial photography, such as Global Position System (GPS) that used to know the vehicle coordinates. This makes Heksacopter fly to some specify coordinates and doing aerial photography automatically. Heksacopter is expected able to fulfil the needs of aerial photography.